Soft, miniaturized, wireless olfactory interface for virtual reality - Liu, Yiming; Yiu, Chun Ki; Zhao, Zhao; Park, Wooyoung; Shi, Rui; Huang, Xingcan; Zeng, Yuyang; Wang, Kuan; Wong, Tsz Hung; Jia, Shengxin; Zhou, Jingkun; Gao, Zhan; et al. (Nature communications, 2023)
Recent advances in virtual reality (VR) technologies accelerate the creation of a flawless 3D virtual world to provide frontier social platform for human. Equally important to traditional visual, auditory and tactile sensations, olfaction exerts both physiological and psychological influences on humans. Here, we report a concept of skin-interfaced olfactory feedback systems with wirelessly, programmable capabilities based on arrays of flexible and miniaturized odor generators (OGs) for olfactory VR applications. By optimizing the materials selection, design layout, and power management, the OGs exhibit outstanding device performance in various aspects, from response rate, to odor concentration control, to long-term continuous operation, to high mechanical/electrical stability and to low power consumption. Representative demonstrations in 4D movie watching, smell message delivery, medical treatment, human emotion control and VR/AR based online teaching prove the great potential of the soft olfaction interface in various practical applications, including entertainment, education, human machine interfaces and so on. Virtual reality technologies need olfactory systems to improve human perception, but their bulky formats limit their practicality. Here, Liu et. al. report flexible and miniaturized odor generators with tunable odor concentration in close user proximity for immersive virtual reality applications.